2006
DOI: 10.1213/01.ane/0000247966.49492.72
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesia After Major Spine Surgery: Patient-Controlled Epidural Analgesia Versus Patient-Controlled Intravenous Analgesia

Abstract: We conclude that PCEA with ropivacaine and sufentanil, using intraoperatively placed epidural catheters, provides superior analgesia and higher patient satisfaction when compared with PCIA after spinal fusion surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 16 publications
2
56
2
3
Order By: Relevance
“…These data are in line with published data of patients with posterior spinal surgery in the noninfectious setting, which demonstrated reduced time to reach turning capacities in bed in patients with epidural analgesia compared with patients with intravenous analgesia. 16 In regard to technical handling of epidural catheters, no complications in the form of disruption of the dura or violation of the spinal cord were observed when visually placing the catheter, which concurs with the literature and the consensus of a more feasible intraoperative catheter insertion compared with a preoperative catheter placement (Table 3). 7 Further, follow-up did not reveal any catheterassociated complications such as respiratory depression or neurological worsening, as has been previously described.…”
Section: Discussionsupporting
confidence: 86%
“…These data are in line with published data of patients with posterior spinal surgery in the noninfectious setting, which demonstrated reduced time to reach turning capacities in bed in patients with epidural analgesia compared with patients with intravenous analgesia. 16 In regard to technical handling of epidural catheters, no complications in the form of disruption of the dura or violation of the spinal cord were observed when visually placing the catheter, which concurs with the literature and the consensus of a more feasible intraoperative catheter insertion compared with a preoperative catheter placement (Table 3). 7 Further, follow-up did not reveal any catheterassociated complications such as respiratory depression or neurological worsening, as has been previously described.…”
Section: Discussionsupporting
confidence: 86%
“…EA had not been used, and mean opioid doses were low compared with those in trials using patient-controlled Iv analgesia that demonstrated an average consumption of 150 mg oral morphine equivalents within the first 24 hours. 17,18 Even though open reduction of the calcaneus-the procedure with the highest pain score in this study-was associated with a comparatively high opioid administration of 40 mg, another trial demonstrated that patients used on average 167 mg Iv morphine via patientcontrolled anesthesia (approximately 500 mg oral morphine equivalents) during the first 24 h. 19 EA and peripheral nerve blocks are known to reduce postoperative pain intensity. 20 For many procedures, especially those that are known to cause severe postoperative pain, guidelines from many countries recommend the use of rA for postoperative pain control.…”
Section: Discussionmentioning
confidence: 69%
“…A total of 136 studies were identified from our electronic database searching and manual searching, remaining 9 studies qualified for our meta-analysis [12,27,[39][40][41][42][43][44][45]. Briefly, we excluded studies for duplicates (n = 1), unrequired article types (letters, reviews, non-human studies, unrelated to research topics and meta-analysis; n = 54).…”
Section: Included Studiesmentioning
confidence: 99%